Can biochar and hydrochar be used as sustainable catalyst for persulfate activation? - Gasim, M.F. (Elsevier Ltd, 2022)
Over the past decade, there has been a surge of interest in using char (hydrochar or biochar) derived from biomass as persulfate (PS, either peroxymonosulfate or peroxydisulfate) activator for anthropogenic pollutants removal. While extensive investigation showed that char could be used as a PS activator, its sustainability over prolonged application is equivocal. This review provides an assessment of the knowledge gap related to the sustainability of char as a PS activator. The desirable char properties for PS activation are identified, include the high specific surface area and favorable surface chemistry. Various synthesis strategies to obtain the desirable properties during biomass pre-treatment, hydrochar and biochar synthesis, and char post-treatment are discussed. Thereafter, factors related to the sustainability of employing char as a PS activator for anthropogenic pollutants removal are critically evaluated. Among the critical factors include performance uncertainty, competing adsorption process, char stability during PS activation, biomass precursor variation, scalability, and toxic components in char. Finally, some potential research directions are provided. Fulfilling the sustainability factors will provide opportunity to employ char as an economical and efficient catalyst for sustainable environmental remediation. Â© 2021 Elsevier Ltd